S130 Outcomes of pseudomonas eradication therapy in patients with non-cystic fibrosis bronchiectasis. (16th November 2010) - White, L; Mirrani, G; Grover, M; Rollason, J; Malin, A; Suntharalingam, J
Abstract : Introduction and objectives: In patients with non-cystic fibrosis (CF) bronchiectasis, Pseudomonas aeruginosa infection is associated with increased hospital admissions, poorer quality of life and accelerated lung function decline. The BTS guidelines recommend early Pseudomonas eradication therapy. However, despite clear evidence in CF, there is little evidence in non-CF bronchiectasis. Since 2004, we have initiated eradication therapy following initial Pseudomonas infection in non-CF bronchiectasis patients. This retrospective study assessed clinical and microbiological outcomes. Methods: All patients undergoing Pseudomonas eradication therapy from 2004 to 2010 were identified from our electronic database. Therapy included intravenous, oral and nebulised antibiotics. Patients were assessed for microbiological eradication, exacerbation frequency (measured by number of antibiotic courses), hospital admissions, clinical symptoms and lung function. Results: 30 patients were identified. 21 (67.7%) were females and mean age was 62.2 years. Median follow-up time was 26.4 months. Eradication therapy involved 2 weeks of intravenous antibiotics (12 patients), intravenous antibiotics followed by oral ciprofloxacin (13 patients) or oral ciprofloxacin alone (five patients), combined with 1–4 months of nebulised colomycin in 26 patients. Pseudomonas was initially eradicated from sputum in 24 patients (80.0%). 13 patients (43.3%) remained Pseudomonas -free at latest follow-up. 11 patients (36.7%) were subsequently reinfected with median time to reinfection of 6.2 months (Abstract S130 Figure 1 ). 17 patients with chronic infection were maintained on regular nebulised antibiotics. Exacerbation frequency was significantly reduced, with mean number of antibiotic courses per year 3.93 pre-eradication, and 2.09 post-eradication (p=0.002). Mean number of hospital admissions per year were similar, at 0.39 pre-eradication and 0.29 post-eradication (p=NS). At first follow-up, 20 patients (66.7%) reported overall clinical improvement, with reduced cough in 12 (40.0%), reduced sputum volume in 14 (46.7%) and reduced sputum purulence in 11 (36.7%). Of the 21 patients followed up to 1 year, 6 (28.6%) had further overall improvement and 13 (61.9 %) remained stable. Lung function was not affected by eradication therapy, with mean percentage predicted FEV1 62.1% pre and 64.1% post-eradication (p=NS). Conclusion: This study demonstrated that Pseudomonas eradication therapy can lead to prolonged clearance of this organism and highly significantly reduces exacerbation rate. This important outcome requires confirmation in a prospective study.